2014
DOI: 10.1108/jmtm-12-2012-0114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Six Sigma methodology to improve logistical measures of food distribution SMEs

Abstract: Purpose – The purpose of this paper is to investigate the implementation of the Six Sigma methodology as a systematic business strategy and quality initiative to improve the critical logistical measures within small-to-medium-sized food distributors. Design/methodology/approach – The first stage was the conducting of structured questionnaires to verify the applicability in terms of capability, resources and culture in the targeted indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 83 publications
2
10
0
4
Order By: Relevance
“…The results presented in this paper have concurred with theoretical research found in the literature that the most important LSS success and failure factors are top management commitment and resistance to change (Shokri et al, 2014;Thomas et al, 2014;Assarlind et al, 2013;Delgado et al, 2010;Desai et al, 2012;Choi et al, 2012;Jayaraman et al, 2012;Lee et al, 2011). In fact, this research study has emphasised the human behavioural-related aspects of these factors and more importantly revealed key human resource elements to support LSS implementation.…”
Section: Research and Practical Implicationssupporting
confidence: 87%
See 2 more Smart Citations
“…The results presented in this paper have concurred with theoretical research found in the literature that the most important LSS success and failure factors are top management commitment and resistance to change (Shokri et al, 2014;Thomas et al, 2014;Assarlind et al, 2013;Delgado et al, 2010;Desai et al, 2012;Choi et al, 2012;Jayaraman et al, 2012;Lee et al, 2011). In fact, this research study has emphasised the human behavioural-related aspects of these factors and more importantly revealed key human resource elements to support LSS implementation.…”
Section: Research and Practical Implicationssupporting
confidence: 87%
“…This research study has been undertaken through rigorous primary data collection in German manufacturing SMEs and has responded to the call for more empirical work to be done within the LSS implementation area of the literature (Shokri et al, 2014;Thomas et al, 2014;Zhang et al, 2012;. The results presented in this paper have concurred with theoretical research found in the literature that the most important LSS success and failure factors are top management commitment and resistance to change (Shokri et al, 2014;Thomas et al, 2014;Assarlind et al, 2013;Delgado et al, 2010;Desai et al, 2012;Choi et al, 2012;Jayaraman et al, 2012;Lee et al, 2011).…”
Section: Research and Practical Implicationssupporting
confidence: 66%
See 1 more Smart Citation
“…For (Shokri, A., Oglethorpe, D. & Nabhani, F., 2014), top management support and employees' acceptance of change positively enhance the successful implementation of SS. In a study conducted on Brazilian companies, (De Carvalho, M., Ho, L. & Pinto, S., 2014) suggested three CSFs of SS implementation, namely, organizational (commitment and resources), infrastructure-related (information systems and statistical tools), and human resource dimensions (internal factors related to employees such as their education and training, and external factors such as consultants).…”
Section: Csfs Of Six Sigmamentioning
confidence: 99%
“…Examples of factors required to successfully adopt SS include customer and process focus, management by fact, clear objectives, and vision of top management (Caulcutt, R., 2001). According to (Shokri, A., Oglethorpe, D. & Nabhani, F., 2014), top management support and employees' acceptance to change are key CSFs of SS adoption. In some cases, the benefits of SS were not as it should be.…”
mentioning
confidence: 99%